2018
DOI: 10.1038/s41375-018-0213-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute lymphoblastic leukemia as a clonally unrelated second primary malignancy after multiple myeloma

Abstract: Multiple myeloma (MM) patients have an 11-fold increased risk of developing myeloid neoplasms compared to the general population; however, acute lymphoblastic leukemia (ALL) is rarely observed. Given that both MM and the majority of ALL are of B cell origin, this raises the question of whether ALL in patients with MM arises from the same clone. We report 13 cases of B-cell ALL following therapy for MM. The interval from MM diagnosis to ALL onset was 5.4 years (range 3.3-10). The median age at the time of ALL d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…Aldoss et al reported 13 patients with ALL after MM treatment (1.3% of all ALL patients) and reported a 1-year OS of 77% in this group. 19 The 2-year OS among patients with B-cell t-ALL after allogeneic HCT in our study (66.7%) is comparable to existing literature on allogeneic HCT outcomes in high-risk de novo ALL. 22 Recent studies have reported favorable outcomes of t-ALL after allogeneic HCT, however, have not separately reported outcomes or impact of allogeneic HCT in patients with a previous history of MM.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Aldoss et al reported 13 patients with ALL after MM treatment (1.3% of all ALL patients) and reported a 1-year OS of 77% in this group. 19 The 2-year OS among patients with B-cell t-ALL after allogeneic HCT in our study (66.7%) is comparable to existing literature on allogeneic HCT outcomes in high-risk de novo ALL. 22 Recent studies have reported favorable outcomes of t-ALL after allogeneic HCT, however, have not separately reported outcomes or impact of allogeneic HCT in patients with a previous history of MM.…”
Section: Discussionsupporting
confidence: 83%
“…Although both B-cell ALL and MM arise from post germinal center B-lymphocytes, t-ALL arising after MM treatment was shown to be a clonally unrelated therapy-related malignancy. 19 Of note, in contrast to t-MDS/AML, there is no evidence of disease-related factors in the development of t-ALL after MM. No cases of ALL were found in a large Swedish population-based study comparing secondary malignancies in patients with MGUS compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, a recent study of 13 t-ALL cases by Aldoss and colleagues reported that t-ALL arising after multiple myeloma is clonally unrelated to the original malignancy. 20 Collectively, the data suggest that different pathogenic mechanisms exist for the development of t-ALL, which may be driven by inherited cancersusceptibility genes in a small subset of patients, whereas other patients develop the disease de novo as a result of genotoxic effects of prior therapies.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study of 13 tr-ALL cases by Aldoss et al analyzed paired samples of multiple myeloma and ALL using whole-exome sequencing and reported that tr-ALL arising in this setting is clonally unrelated to the multiple myeloma, supporting the notion that it represents a therapy-related leukaemia. 13 Further research on tr-ALL in patients with antecedent multiple myeloma is warranted.…”
Section: Discussionmentioning
confidence: 99%